2019
DOI: 10.1016/j.heliyon.2019.e02833
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Hansen solubility parameter in evaluating transparency of composite materials

Abstract: A B S T R A C TIn the preparation of polymer-based functional materials, it is often difficult to express the desired function using a single substance. Thus, multiple materials are often combined to achieve a desired function using methods such as the addition of a filler or lamination. However, when materials are mixed using a filler, the transparency of the polymer decreases. Therefore, a prediction indicator for transparency is needed. In this study, we focused on using the Hansen solubility parameter (HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
(40 reference statements)
0
8
0
Order By: Relevance
“…In particular, the predicted dD, which indicates the dispersion energy, showed a relatively high accuracy. It was assumed that this was due to the use of the experimental refractive index value as training data, which is closely related to the weight per unit volume, density, and dD . Actually, the refractive index is the most important factor in the case of the dD prediction (Figure , Table S6a).…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the predicted dD, which indicates the dispersion energy, showed a relatively high accuracy. It was assumed that this was due to the use of the experimental refractive index value as training data, which is closely related to the weight per unit volume, density, and dD . Actually, the refractive index is the most important factor in the case of the dD prediction (Figure , Table S6a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…It was assumed that this was due to the use of the experimental refractive index value as training data, which is closely related to the weight per unit volume, density, and dD. 51 Actually, the refractive index is the most important factor in the case of the dD prediction (Figure 3, Table S6a). The dispersion energy dD is a weak intermolecular force that acts even for non-polar molecules, unlike the dipole moment dP.…”
Section: Dnn Solubility Prediction 2-mentioning
confidence: 99%
“…As characterization of NP dispersibility, Hansen solubility parameters (HSP) or Hansen dispersibility parameters (HDP) have been adopted to obtain a deeper insight into the surface properties of NPs. ,,, Fujiwara et al reported the surface modification of copper NPs using silane coupling agents and estimated the alteration of their surface properties based on HSP . Although the correlation between the degree of surface modification and surface properties was unclear, the HSP value of surface-modified NPs became closer to that of the modifier.…”
Section: Introductionmentioning
confidence: 99%
“…Although HSP has nonetheless proved a powerful characterization tool for predicting NP dispersibility, the HSP characterization is a time-consuming process because it generally requires ca. 20 kinds of solvents for the dispersibility test. ,, As another approach to obtain the local surface properties of materials, solvatochromic dyes are useful. Pyrene derivatives, betaine derivatives, and naphthalene derivatives have been utilized to investigate the micropolarity in blend polymer, silica NPs, and lipid self-assemblies, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, a linear correlation to predict the particle size in the final aqueous phase from the Hansen solubility parameters of the organic solvent blends was investigated. These studies were performed since the particle dispersibility [22,23], transmittance [24] or particle sizes have only been studied in organic solvents [25] from the Hansen solubility parameters.…”
Section: Introductionmentioning
confidence: 99%